Determination of Minerals and Anti-Nutritional Factors of Some Lesser-Known Crop Seeds - Ilelaboye, N.O.A.; Pikuda, O.O. (Pakistan Journal of Nutrition, 2009)
The cost of raw material needed for the production of animal feed has led to the evaluation and ascertaining the adequacy of some lesser known crop seeds for minerals composition and the possible effects of anti nutritional factors on the availability of the required nutrients. The mineral elements and anti nutritional factors Jatropha curcas, Trichosanthes cucumerina, Citrillius vulgaris, were determined using standard analytical methods. The concentration of copper (16.00 mg/kg-43.00 mg/kg), Zinc [33.00 mg/kg-45.00 mg/kg], Manganese [51.70 mg/kg-63.00 mg/kg], Potassium [8704.15 mg/kg-9246.33 mg/kg], Sodium [170v mg/kg-206. mg/kg], Phosphorus [322.20 mg/kg-411.60 mg/kg], Iron [133 mg/kg-187 mg/kg], Magnesium [1896.00 mg/kg-2394 mg/kg] and Calcium [1534.00 mg/kg-1826.00 mg/kg], varied significantly in the seeds respectively. The content of the minerals in metabolize state were greatly affected by the anti-nutritional factors, tannin [7.50 mg/100 g-25.30 mg/100 g], saponin [1100.00 mg/100 g-2097 mg/100 g], oxalate [17.40 mg/100 g-40.65 mg/100 g], nitrite [50.30 mg/100 g-57.30 mg/100 g], nitrate [9.00 mg/100 g-24.60 mg/100 g] and phytic acid [480.03 mg/100 g-2012.02 mg/100 g]. Concentration of mineral elements in all lesser known crop seeds are below the dietary requirements for animal.